Gallium chiral nanoshaping for circular polarization handling. Issue 1 (9th November 2020) - Cuscunà, Massimo; Manoccio, Mariachiara; Esposito, Marco; Scuderi, Mario; Nicotra, Giuseppe; Tarantini, Iolena; Melcarne, Angelo; Tasco, Vittorianna; Losurdo, Maria; Passaseo, Adriana
Abstract : Core/shell nanohelices with VIS-CD are grown using FIBID, with the Ga + source shaping the metallic core and the gas precursor the dielectric shell Abstract : In this work we report the local growth of ordered arrays of 3D core–shell chiral nanohelices based on plasmonic gallium metal. The structures can be engineered in a single step using focused ion beam induced deposition, where a Ga + ion source is used to shape the metallic nanohelix core, while the dielectric precursor is dissociated to create dielectric shells. The solubility of gallium in the different investigated dielectric matrices controls the core–shell thickness ratio of the nanohelices. The chiral plasmonic behaviour of these gallium-based nanostructures is experimentally measured by circularly polarized light transmission through nanostructure arrays and compared with numerical simulations. Large chiroptical effects in the visible range are demonstrated due to the plasmonic effects arising from gallium nanoclusters in the core.